Peningkatan Pemahaman Siswa Tentang Materi Salat Jumat melalui Metode Role Playing di MTs Roudhotul Huda - Latifatun Hamidah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to improve students' understanding of Friday prayer material through the application of the role playing method in class VII MTs Roudhotul Huda. The background of this study is the low learning outcomes of students on Friday prayer material as indicated by daily test scores and minimal participation in class discussions. This study uses a Classroom Action Research (CAR) approach consisting of two cycles. Each cycle includes planning, implementation of actions, observation and reflection. The instruments used include pre-test and post-test, observation sheets, and documentation of the learning process. The results of the study indicate that the role playing method can significantly improve students' understanding and increase student activity during the learning process. Thus, the role playing method is effective for use in fiqh learning, especially Friday prayer material.